Tax Avoidance in the Perspective of Diamond Fraud Theory and Its Consequences on Firm Value with Mediating Variables of Financial Distress and Ethical Management - Jaeni, Jaeni; Fadhila, Zati Rizka; Rahmadhani, Sari (Indonesia Accounting Research Journal, 2024)
The research problem, namely empirical testing regarding fraud diamonds consisting of (a) pressure, (b) opportunity, (c) rationality, and (d) capability, may be the underlying reason for corporate tax avoidance. On the other hand, companies will experience financial difficulties so the intensification of financial distress within a company will lead the company to carry out tax avoidance. Fraud opportunities to commit tax avoidance can be realized if company managers do not carry out ethical management. The aim of the research is to obtain empirical evidence of Tax Avoidance from the Fraud Diamond Theory Perspective, and its consequences for firm value with the Mediation variables of Financial Distress and Ethical Management. The results of financial distress research become a mediating variable. Tax avoidance as Y1 while Christian (2020) corporate fraud. Even though corporate fraud cases have often been researched in the Asia Pacific region, especially China, in Southeast Asia there is still very little research or literature that examines tax avoidance cases using the fraud diamond approach with moderation of financial distress. Among other things, there is a significant positive influence of tax amnesty on tax avoidance, the influence of tax avoidance has a significant positive effect on firm value, a significant negative effect of tax amnesty on firm value, and tax avoidance is not a mediating variable for the effect of tax amnesty on firm value.